THE EFFECT OF SELF-EDITING ON WRITING SKILL OF TWELFTH GRADE STUDENTS OF SMAN 1 LUBUKLINGGAU - Rismar Riansih (EduLite: Journal of English Education, Literature and Culture, 2017)
Self-editing has been considered an important part of writing process that helps improving writing ability and yet become a better writer. This is because by having self-editing, the students are able to recognize their own errors in their composition. Therefore, this current study was conducted to investigate the effect of self-editing on writing skill of twelfth grade students of SMAN 1 Lubuklinggau. The subject of this study consisted of 34 students of grade XII IPA 3. It was found that after experiencing the writing instruction with self-editing, the students’ writing skill improved significantly. The students have been very enthusiastic towards the teaching technique. Their score in writing increased from pre-test to the end of cycle II.  The result of pre-test showed that the average was 68. From 34 students in the class, only 7 students got the score   above 79 and 27 students got the score bellow 79. In addition, in cycle I, the students who got the score above Minimum Mastery Criteria were 12 or 35, 29% and those who got below the Minimum Mastery Criteria that were 22 or 69, 71%.  The average was 75. Finally, in cycle II, the students who got score above Minimum Mastery Criteria were 30 or 88. 24% and those who got below Minimum Mastery Criteria were 4 or 11. 76%.  The average score was 81.32. Hence, it can be concluded that self-editing is indeed effective in improving the writing performance of the students. In addition, they could make further revisions on their own errors. Through self-editing, the students were willing to provide further support to peers and learn from each other in the process of writing.Keywords: Self-editing, Discussion text, Writing